PERLINDUNGAN HUKUM TERHADAP HAK WARIS ANAK PADA PERKAWINAN DIBAWAH TANGAN - Sartika Rahman (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractThe Indonesian people recognize the term underhanded marriage as a legal marriage in Islamic law but are not stated in the KUA (Office of Religious Affairs), so the validity of the marriage is not recognized by the state. One of the negative effects caused by marriage under the hands is the absence of binding legal power over the marriage, the State considers that the marriage under the hand never existed, because there was no evidence in the form of a marriage certificate. Underage marriage can also cause problems regarding the inheritance of children.The type of research used in this paper is the type of normative juridical research with a Statute Approach and Conceptual Approach.The results of the study showed that children born of marriage under the hand were basically legitimate children. This is based on Law Number 1 of 1974 concerning Marriage and the Compilation of Islamic Law. The inheritance rights of children born into marriages under the hand have been settled through the Decision of the Constitutional Court of the Republic of Indonesia Number 46 / PUUVIII / 2010. Before the decision of the Constitutional Court, a child born from marriage under the hand can get an inheritance if both parents carry out a marriage certificate or if their father gives a will to the childKeywords: Inheritance of children, marriage